CONTEXTUAL ANALYSIS OF LOCAL CULTURE IN THE ERA OF GLOBALIZATION ACCORDING TO THE PERSPECTIVE OF THE MILLENNIAL GENERATION - Muhtar; Nurainy Latuconsina, Joana Joanita Tuhumury (Adisam Publisher, 2024)
In facing increasingly complex global challenges, having a deep understanding of cultural identity can be an invaluable asset. The millennial generation has the potential to be a powerful bringer of change by combining indigenous cultural wisdom and global insight. As a generation that continues to move forward in the modern era, the millennial generation's tendency to gain inspiration from foreign cultures cannot be ignored. This phenomenon, although controversial, reflects a drive for exploration and openness to the wider world. However, in this journey, it is important for the millennial generation not to forget their own cultural roots. Indigenous culture is a milestone of identity that connects the past with the future, reminding us of our rich historical roots and precious heritage. The millennial generation can enrich their knowledge about their own culture. Apart from being preserved in two forms, local culture can also be preserved by getting to know the culture itself. In this way, at least cultural piracy can be anticipated by other countries. The problem that often occurs in society is that sometimes they don't feel proud of their own products or culture.